4‐Amino‐1‐Butyl‐1, 2, 4‐Triazolium Dinitramide – Synthesis, Characterization and Combustion of a Low‐Temperature Dinitramide‐Based Energetic Ionic Liquid (EIL). Issue 7 (20th May 2022) - Schaller, Uwe; Lang, Johannes; Gettwert, Volker; Hürttlen, Jürgen; Weiser, Volker; Keicher, Thomas
Abstract: Salts being liquid below 100 °C are defined as ionic liquids. Due to their unique properties, they are attracting increasing interest and are also being investigated in the field of energetic materials. Combining nitrogen‐rich cations and oxygen‐rich anions, it is possible to obtain energetic ionic liquids (EILs). Potential applications are plasticizers, high explosives, gun and rocket propellants. However, only few works have been done in the field of EILs which show a glass transition temperature less than −40 °C, the so called low‐temperature EILs (LT‐EILs). LT‐EILs with dinitramide as an anion are an almost unknown group with interesting properties and potential. In this paper we present synthesis, characterization and combustion properties of 4‐amino‐1‐butyl‐1, 2, 4‐triazolium dinitramide (C4 DN) as a low temperature dinitramide‐based EIL in its entirety for the first time. A classic synthesis route and a metal‐free route are presented. The physical properties were measured and compared to conventional non‐ionic energetic plasticizers like BDNPA/F, TMETN/BTTN, Bu‐NENA and DNDA‐57. The combustion behaviour was studied using an optical window bomb and compared to non‐ionic energetic liquids in use. To evaluate the performance as an energetic plasticizer or additive, the interaction with the energetic binder GAP is investigated by manufacturing of dog bone‐shaped test specimen and comparing their mechanical properties and their glass transition temperatures with conventional energetic plasticizers, based on non‐ionic energetic compounds. As one result, C4 DN showed an intense softening effect. Based on the result, propellant samples were prepared and characterized. Abstract :